Evaluation of the Implementation of the Greenship Neighborhood Concept Version 1.0 in the Pahlawan Tuanku Tambusai University Campus Area - Febrianty, Nanda Lelis; Adeswastoto, Hanantatur; Rusnedy, Hidayati (Journal of Engineering Science and Technology Management, 2025)
This study aims to evaluate the implementation of the Greenship Neighborhood version 1.0 concept at Pahlawan Tuanku Tambusai University Campus. The evaluation was carried out to determine the level of application of sustainability principles, which include aspects of land ecological enhancement, movement and connectivity, water management, waste management, community wellbeing, energy efficiency, and innovation. The research employed descriptive qualitative and quantitative methods through field observations, interviews, and documentation. The collected data were analyzed based on the Greenship Neighborhood assessment criteria established by the Green Building Council Indonesia (GBCI). The results indicate that the implementation of the sustainable neighborhood concept at Pahlawan Tuanku Tambusai University has been carried out quite well but still requires improvement in several aspects, particularly in energy efficiency and land ecology management. The campus has shown a real commitment to sustainable development through the provision of green open spaces, environmental management systems, and public facilities that support the comfort and wellbeing of the academic community. Based on the evaluation results, the campus area obtained a score that falls into the Bronze category in the Greenship Neighborhood rating system. This research is expected to serve as a reference for developing a more environmentally friendly and sustainable green campus in the future.